Documentation of labor contracts in Saudi law - Alzahrani, Rashed Eidhah (Journal of Economic, Administrative and Legal Sciences, 2022)
The Ministry of Human Resources and Social Development, in light of achieving the vision of the Kingdom of Saudi Arabia 2030, has launched several initiatives to guarantee the rights of the labor and the employer, the most important of which is the initiative to document work contracts, which obliges all employers to document their employees’ contracts on electronic platforms for this, such as Mudad platform, and the General Organization for Social Insurance (GOSI), and Qiwa platform, and since the initiative is recently established, I thought that my research should be in the study of the dimensions of the initiative in terms of identifying the nature of documenting work contracts, as well as the mechanism used for documenting contracts through the inductive approach of decisions and regulations issued that regulate the documentation of work contracts in the Saudi law.
Keywords: documenting contracts; work contracts; initiative of the Ministry of Labor; extended platform; strong platform